The nexus between covid-19 and stock returns: evidence from selected mena countries - ÖNER, MEHTAP; AYBARS, ASLI (My University, 2022)
This study investigates the relationship between COVID-19 measured by growth in number of weekly confirmed new cases and stock returns of the major indices in selected Middle East and North Africa (MENA) countries. To test the influence of COVID-19 on stock returns, this study uses panel data methodology using weekly data between 19 March 2020 and 31 December 2020. Contrary to expectations, our findings fail to demonstrate a significant link between stock market index returns and COVID-19, which is proxied by the growth in weekly confirmed new cases. Additionally, regarding the control variables, whereas no relationship is documented between Chicago Board Options Exchange Volatility Index (VIX) and selected countries’ stock index returns, 5-year Sovereign Credit Default Swap (CDS) figures of the selected countries are found to be negatively and significantly related with the main variable of interest.
Keywords: COVID-19; MENA Countries; Panel Data; Stock Return